The palaeo-ichnology of the Miocene deposits in the Romanian Carpathians: A short overview of existing data referring to the uncovered footprints of vertebrates in the Miocene deposits, their taxonomy, a hypothesis regarding the paleo-environmental condition within the region and the genesis of these deposits (Geo-Eco-Marina, 2022)
The paper refers to the paleo-ichnology of the Miocene Molasse deposits in the Romanian Carpathians. The principles of systematics and nomenclature of the vertebrate traces from these deposits are briefly presented. Follows a review of the ichno-fossiliferous points in the Carpathians, with a complete inventory of the traces discovered in each ichno-fossiliferous region. In the next chapter, the vertebrate tracks are described and each ichnospecies is illustrated. In the end, the article presents a hypothesis regarding the formation of the flish-like Miocene Molasse deposits having footprints of vertebrates coexisting with mechanical traces generated by strong currents (scour - and tool-marks) but also with wave ripple-marks and traces of rain drops. The present article is actually a synthesis of the papers published in 1961, 1962, 1964, 1965, 1966 and 1968 by N. Panin and N. Panin in collaboration with other researchers.
Keywords: Paleo-ichnology; Miocene Molasse; taxonomy; paleo-environmental conditions; turbidity flood currents